Forensic Assistance Project: Consultant Report 1999-079 Sarajevo IV Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Polli, Maura On 16 and 17 November the Republika Srpska Commission on Tracing Prisoners and Missing Persons visited sites around Sarajevo to conduct exhumations. The remains of six individuals were exhumed. Place of Exhumation: Sarajevo Exhumation Site: Dobrinja II-A, Dobrinja II-B, Semizovina Cemetery, Pojalići Date of Exhumation: 16-17 November 1999 Minimum Number of Exhumed Individuals: 006